ANALYSIS OF ZIGGY CONSTRUCTION'S MARKETING STRATEGY IN COMPETING WITH OTHER COMPETITORS - Mutia Salsa Billa; Herry Goenawan Soedarsa (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
The purpose of this study is to study marketing strategies used by Ziggy Construction in the face of competitiveness against other competitors. This research uses a mixed method, or a combination of two research methods simultaneously both quantitative and qualitative. Mixed method is intended to obtain more valid, reliable, and objective data. This research is descriptive following the process of data collection, writing, and explanation. This study used data collection techniques based on field research. Based on the results that have been described, Ziggy Construction uses the SWOT analysis method with IFAS and EFAS and the matrix diagram obtained is in quadrant 1 (one) meaning that the right strategy in the quadrant is an aggressive growth policy (Growth Oriented). The conclusion that can be drawn in this study is the marketing strategy used by Ziggy Construction in facing competitiveness against other competitors, namely by utilizing social media as a promotional event to introduce services to consumers, utilizing technology to manage financial statements to be more efficient and accurate, providing the best service to consumers to be more satisfied, and providing prices that are relatively cheaper than other competitors.